(untitled) (Quinto Sol, 2016)
From the first decades of the 20th century, the creation of the "communityhospital" was part of the projects of the leadership of the Asociación Española de Socorros Mutuos based in Comodoro Rivadavia. Resumed en 1947, it culminated with the inauguration of the clinic of their own in 1959. This article analyzes how managerial commissions of the ethnic groups of the study area found, in the field of health care demands, a land fit to expand voluntary associations. In the early 1940s there was a keen interest on the part of the central State in regulating the associational life, a situation which, in principle, was received with appreciation by local leaderships. However, the creation of the Directorate of mutuals and the attempt by the Secretariat of Labour and Welfare that the mentioned entities accounted for the conditions of its inner workings culminated with the rejection of the leadership of the Galician Centre of Comodoro Rivadavia and the Spanish Association. The studied Spanish associations have a significant documentary heritage, which, coupled with the local press consulted, will enable us to bring us closer to the particularities of the associations in the area. Our work is part of a renewed interest of local academics, and, above all, balance collective performed on one side of the Atlantic Ocean.